The Degree of Effectiveness of Blended Learning in Teaching Mathematics to Students of the First Three Grades: Teachers' Point of View - Alkhabayba, Rawan Awad Mohammad (Dirasat: Educational Sciences, 2023)
Objectives: From the point of view of students' teachers, the study identifies the effectiveness of blended education in teaching mathematics to students in their first three grades. Methods: During the second semester of the academic year 2021/ 2022, a randomly selected sample of teachers of the first three grades at the Mark District Directorate in Amman, Jordan. In total, a sample of (250) female teachers from the first three grades were selected. The validity and reliability of the study tool were examined after the distribution of a questionnaire consisting of (31) items. The degree of effectiveness was judged by the following criterion: arithmetic average from (1) to (2.33) with low potency, (2.34) to (3.66) with medium, and (3.67) to (5) with high efficiency. Results: Results showed that students in the first three grades benefited in mathematics from blended learning by a moderate (3.58 + 0.45) amount, from their teachers' point of view. The results also indicated no statistically significant differences for the variables of educational qualification and years of experience. It is necessary to consider the challenges in the field, such as the fact that despite their educational background, most stage teachers lack computer skills, as well as the scarcity of educational resources for using of e-learning teaching strategies, including interactive whiteboards, computers, and the internet. Conclusions: The study recommends conducting training courses for primary school teachers to develop their computer skills and provide the necessary techniques to activate e-learning.